SCREENING MAMMOGRAPHY PERFORMANCE OF 2D DIGITAL MAMMOGRAPHY VERSUS BREAST ULTRASONOGRAPHY IN WOMEN WITH DENSE BREAST (The Research of Medical Science Review, 2025)
This study aimed to evaluate and compare the performance of 2D digital mammography and breast ultrasonography in detecting breast cancer among women with dense breast tissue, categorized as BI-RADS C (heterogeneously dense) and D (extremely dense). Dense breast tissue presents significant challenges for accurate mammographic detection, necessitating the investigation of alternative or supplementary screening approaches. A cross-sectional study design was implemented, recruiting participants from imaging centers. Eligible women with dense breasts underwent both 2D digital mammography and breast ultrasonography after providing informed consent. The primary outcomes assessed were breast cancer detection rates, false-positive rates, sensitivity, and specificity of each screening modality. Data were collected through medical records and imaging results, with follow-up evaluations to capture subsequent diagnostic interventions. The comparative analysis focused on the accuracy of each method in identifying breast abnormalities within dense tissue, emphasizing true-positive rates, false-positive rates, sensitivity, and specificity. The findings revealed that both 2D digital mammography and breast ultrasonography offer valuable contributions to breast cancer detection, particularly when used in combination. While mammography demonstrated a higher false-positive rate and was associated with physical discomfort, ultrasonography resulted in lower patient satisfaction and heightened emotional distress, especially among high-risk individuals. Despite these limitations, integrating both modalities improved early detection rates and enhanced overall patient outcomes. The study underscores the importance of a tailored, multimodal approach to breast cancer screening for women with dense breast tissue.